Clinical pharmacy services in acute care setting during mass gatherings (Hajj): Insights from a task force - Ohoud Aljuhani; Khalid Al Sulaiman; Abdulkareem M.Al Bekairy; Khalil Almajed; Mahasen Al Harbi; Abrar K. Thabit; Abdullah F. Alharthi; Namareq Aldardeer; Hisham A. Badreldin; Abdullah M. Alhammad; Ahmed O. Alenazi; Badr Alghamdi; et al. (Elsevier, 2024)
Background: Hajj is the largest mass gathering worldwide that takes place every year in Makkah, Saudi Arabia. This paper aims to provide a comprehensive guide and expectations for delivering and optimizing clinical pharmacy services during one of the largest mass gatherings in the world, Hajj pilgrimage Methods: A task force initiated and included members of clinical pharmacists who previously participated in delivering clinical pharmacy services during the Hajj pilgrimage, members of the Saudi Society of Clinical Pharmacy (SSCP), and policymakers from different sectors and representatives from pharmaceutical care of the Ministry of Health (MOH). The members established an expert task force to conceptualize and draft the proposed suggestions highlighting the roles and responsibilities of clinical pharmacists during the annual Hajj season. Results: The task force determined the following key domains 1) pharmaceutical care (administration and strategic plan, resources, formulary management); 2) pharmacists' activities (clinical pharmacy services and documentation, professional training and development, and staff credentials, and qualifications); 3) challenges and proposed solutions. The task force was divided into groups to draft each domain and provide suggested statements and insights for each section. Finally, the group members of the task force issued 15 opinion statements. Conclusion: Mass gatherings such as Hajj pilgrimage, represent a unique opportunity to demonstrate the value of pharmacists in advancing health care delivery within a multidisciplinary team. These suggestions and insights could guide the implementation of clinical pharmacy services in acute settings during mass gatherings (Hajj). Future studies should focus on assessing the applicability and the impact of the provided suggestions.